Improved angle accuracy of tibial plateau osteotomy for total knee arthroplasty using tibial mechanical axis skin-mapping - He, Peiheng; Huang, Shuai; Liu, Yong; Li, Xing; Xu, Dongliang (Frontiers in Surgery, 2023)
Background The tibial crest is often used as an anatomic landmark for tibial plateau osteotomy (TPO) in total knee arthroplasty (TKA), but it is not very accurate. This study aimed to investigate errors in using the tibial crest as a marker and present a simple approach to improve the angle accuracy of TPO by mapping the tibial mechanical axis (TMA), determined preoperatively, according to the tibial crest on the skin overlying the tibia. Methods We evaluated 50 healthy young volunteers and 100 pre-TKA osteoarthritic knees. The middle tibial crest lines (MTCLs) were marked on the shank tibial skin and covered with Kirschner wires. All participants underwent two sets of anteroposterior (AP) standing radiographs of the lower extremity, with the feet in neutral and external rotation positions. The MTCL–TMA angles were measured and compared. The TMA was mapped onto the tibial skin according to the MTCL–TMA angle prior to TKA and used for TPO. Postoperative outcomes were determined by the angle between the vertical tibial component axis (TCA) and the TMA. Results The MTCL had no evident relationship with the TMA. A few MTCLs were parallel to the TMA. External rotation of the foot significantly changed the MTCL–TMA relationship. The angle accuracy of the TPO as guided by TMA skin-mapping was 0.83 ± 0.76°. No postoperative errors exceeded 3°. Conclusion The MTCL was not equivalent to the TMA. The TPO error can be reduced by preoperatively marking the TMA on the tibial skin according to the MTCL.